Kecemasan belajar aljabar pada generasi Z di era kemajuan teknologi: Analisis pola pikir dan tantangan pembelajaran matematika - Anggraini, Ninin Nafa (Maliki Interdisciplinary Journal, 2026)
The advancement of digital technology has significantly transformed Generation Z’s learning patterns in mathematics, particularly in algebra. As a generation raised in a technology-oriented environment, Generation Z tends to exhibit fast-paced, visual, and digitally integrated learning characteristics. While this condition provides broader access to learning resources, it also creates several challenges, including learning distractions, dependence on instant solutions, and increasing mathematics anxiety. This article aims to analyze the relationship between algebra learning anxiety, students’ mindset, Generation Z characteristics, and technological development in mathematics learning. The study employed a literature review approach by examining national and international journal articles published within the last 5–10 years. The collected data were analyzed using conceptual and critical analysis approaches. The findings indicate that mathematics anxiety affects students’ reasoning ability, conceptual understanding, and problem-solving skills in algebra learning. Furthermore, metacognitive skills and self-regulation play important roles in helping students cope with the challenges of mathematics learning in the digital era. Therefore, interactive, adaptive, and reflective learning strategies are necessary to create more effective mathematics learning that aligns with the characteristics of Generation Z.